Development of a rational composition of a polyenzyme composition in the technology of bioscouring of cotton fabrics - Ksenia A. Lenko; Natallia N. Yasinskaya; Natallia V. Skobova (Vestnik of Vitebsk State Technological University)
In recent decades, research into biochemical methods of preparation of textile materials from cellulose fibers has intensified. Of particular practical importance in terms of environmental friendliness and cellulose preservation are enzymes active at low temperatures and in neutral media. Thus, the authors conducted research on bioscouring of cotton fabrics with polyenzyme compositions consisting of Belarusian preparations (Ferment LLC) of cellulolytic and pectolytic action, during which unacceptable losses of material strength after treatment were observed.